PENGARUH PEMBERIAN TERAPI BREATHING AND IMAGERY EXERCISE TERHADAP PENURUNAN STRESS PADA SISWA KORBAN BULLYING DI SMP N 2 JEPARA - Pratiwi, Anindia; Akbar Amin Abdullah; Ratna Ratna (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Based on a preliminary study on May 30, 2025 through interviews with 10 students of SMP Negeri 2 Jepara, it was found that 7 students had experienced bullying from classmates or from other class students. Objective: to determine the effect of Giving Breathing Therapy and Imagery Exercise on Stress Reduction in Students Victims of Bullying at SMP N 2 Jepara. Method: This type of research is quantitative research with the Quasy experiment method. The design used in the study is One Group Pretest-Posttest. The sampling technique in this study is non-probability sampling. The number of samples in this study was 39 respondents. Results: The results of statistical tests with the Wilcoxon test obtained a p value (0.000) <α (0.005) where the p-value is smaller than the alpha value and Ha is accepted. Conclusion: the results of the study concluded that there is an effect of giving breathing therapy and imagery exercise on stress reduction in students who are victims of bullying at SMP N 2 Jepara.